Caçadores de sentidos : ressignificação do verbete - Santos, Jaci dos (2020)
We often look for instruments, in teaching, that increase the level of student (multi) literacies (ROJO, 2008; KLEIMAN, 2014; DUDENEY, 2016). With different goals, teacher and student become sense hunters in order to improve the process teaching learning. Detected in proposed survey to 9th grade students, from a public school in Aracaju City, their difficulty in understanding semantic aspects of words, in distinguishing textual genres as the entry from other texts and differentiating verse text from prose text. Given this, we propose didacticpedagogical intervention emphasizing the comprehension of semantic aspects present in the written text, specifically synonymy and polysemy, using work with the textual genre entry (DIONÍSIO, ROJO, MARCUSCHI) adopting the perspective of writing as a process (PASSARELI, 2012; SOARES, 2009). This didactic-pedagogical project, developed in PROFLETRAS systematized with didactic sequence (DOLZ e SCHENEUWLY, 2004; MARCUSCHI, 2008) work with both dictionary and encyclopedia entries, exploring its features in print and virtual media like Wikipedia (DUDENEY, 2016), culminating with text writing. Besides that, we materialized the Verbeting game in the text, whose goal is to redefine in a playful way the Portuguese language class, encouraging dictionary consultation. Through experimenting with this game, the structure of the entry is explored, the synonymous and polysemic aspects of terms in a dynamic and interactive way. Therefore, this didacticpedagogical proposal leads the student to the habit of consulting entries and helps him to read and construct texts proficiently.